Practical and facile approach towards indole alkaloids: (-)-mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, Rasapalli; Kalkote, Uttam R. (Synlett, 2007)
An efficient approach to (-)-mitralactonine using Pictet-Spengler cyclisation with a highly functionalised masked aldehyde is described. Sharpless asymmetric dihydroxylation (SAD) is utilised to introduce chirality in the key substrate.
Keywords: alkaloids; asymmetric; cyclisations; dihydroxylations; thioacetats

Formal Synthesis of Corynanthe Indole Alkaloid (±)-Mitralactonine: Construction of α-Hydroxy-Keto Functionalized Tetracyclic Skeleton - Dumare, Nilesh B.; Sharma, Pallavi; Sivappa, Rasapalli; Chavan, Subhash P. (Chemistryselect, 2025)
An efficient synthesis of a tetracyclic skeleton common to many corynanthe alkaloids was accomplished in 10 linear steps starting from a known tetrahydro beta-carboline intermediate. The tetracyclic alpha-hydroxy keto functionalized advanced precursor of (+/-)-mitralactonine was realized using Wittig olefination, ketohydroxylation of a trisubstituted alkene, and a tandem amine unmasking-intramolecular nucleophilic displacement reaction for C-N bond formation of C/D-rings.
Keywords: alpha-hydroxy keto; beta-carboline; corynanthe alkaloid; intramolecular N-alkylation; mitragynine